Comparative Analysis of Wollastonite‐Diopside Glass‐Ceramic Structures Fabricated via Stereo‐Lithography. Issue 6 (25th February 2019) - Elsayed, Hamada; Schmidt, Johanna; Bernardo, Enrico; Colombo, Paolo
Abstract : One key feature of digital light processing consists of the high flexibility in the design of highly porous reticulated scaffolds. In the present paper, the authors report recent experiences concerning two glasses, both converted into wollastonite‐diopside (CaSiO3 –CaMgSi2 O6 ) glass‐ceramics by viscous flow sintering of fine powders (<45 μm) with concurrent crystallization. Glass particles are homogeneously dispersed in a photosensitive polymer, selectively hardened, layer‐by‐layer, by exposure to visible light, forming diamond cell lattices. The printing accuracy is slightly influenced by the glass chemistry, whereas the shape maintenance, after firing at 1100 °C, is observed for both compositions. The newly developed scaffolds are compared to other glass‐ceramic scaffolds, previously developed on the basis of the starting glass: the adoption of a new design does not determine any substantial degradation of mechanical properties. Abstract : Digital light processing provides a high design flexibility in the manufacturing of porous reticulated scaffolds. The authors report recent experiences on two glasses, both converted into CaSiO3 –CaMgSi2 O6 glass‐ceramics, by sintering of fine powders with concurrent crystallization. The printing accuracy is slightly influenced by the glass chemistry, whereas the shape maintenance, after firing at 1100 °C, is observed for both compositions.